Adaptation strategy of Indonesian people in southern Thailand during the Covid-19 pandemic - Turistiati, Ade Tuti; Dayanti, Sekar P.; Priyanto, Dedi; Sumartono (Faculty of Communications Science, Dr. Soetomo University, 2023)
During the Covid-19 outbreak, lockdown regulations affected the mobility of Indonesians temporarily residing in southern Thailand. This study intends to investigate the difficulties they encountered, how they adapted to cultural differences in Thailand, and how they handled with an unpredictable living situation. Case study qualitative research approach was used to conduct the study. The results of the study showed that Indonesian citizens in Southern Thailand found problems related to: 1) Thai language and letters, 2) homesickness, 3) fear of being infected with Covid-19, 4) less halal cuisine is available for Muslims, 5) Worrisome reports in the media regarding the devastating effects of Covid-19. Their adaptation strategy is to: 1) recognize the cultural parallels between Indonesia and Thailand, 2) Develop close relationships between Indonesians in Thailand and their family, relatives, and friends. 3) Think positively, as Covid-19 will soon be finished, 4) Follow a new culture to avoid the spread of Covid-19.